Characterization of Functionalized Low Density Polyethylene/Polyaniline Nano Fiber Composite - Mohib Reza, Kazimi; Saidatul Shima, Jamari; C. K. M., Faizal; Tahir, Shah (Engineering and Technology Publishing, 2014)
Nano composite based on polyaniline (PANI) nano fibers filler and chromic acid functionalized low density polyethylene (LDPE) matrix with biocompatibility and low percolation threshold value was prepared via twin screw extrusion process. Density measurement, Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Electron Microscopy (FESEM), Energy-dispersive X-ray spectroscopy (EDX), X-ray crystallography (XRD), Brunauer, Emmett and Teller analysis (BET), Thermo Gravimetric (TGA), Differential Scanning Calorimetery (DSC) and Four-Probe Conductivity measurements are reported. As low density polyethylene functionalization renders LDPE more biocompatible, it also facilitates conductivity due to carbon carbon double bonds, sulfonic, and carbonyl group moieties. PANI nano fibers also assist in charge transfer mechanism of resultant composite. Overall results indicate the formation of highly stable nanocomposite materials, with good physiochemical properties and conductivity. The resultant blend may prove beneficial as a low cost biocompatible and electrically simulated nerve tissue repair scaffolds.